Dialect Stigma and Group Conflicts - KAOUACHE, Salah (Journal of Human Sciences, 2009)
As the quotation above indicates, social prejudices held on languages in general and dialects in particular are longstanding, and, despite the advance in the domain of sociolinguistics, they continue to exist. It seems that people do not see any reason to stop telling jokes and funny stories about regional dialects and evoking social stereotypes which go far beyond language itself. This problem exists as a product of society. The dialects of Liverpool and Birmingham, for instance, are vivid examples which are looked down in England. Similarly, the dialect of Jijel is a vivid example of the sort in Algeria.The aim of this paper is to support, through an analysis of the attitudes towards the dialect of Jijel, the standpoint that all languages are equally good and that any judgements, therefore, as to the superiority or inferiority of a particular dialect are but social judgements, not linguistic ones.